2011
DOI: 10.1007/s10389-011-0468-5
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of school-based life skills programmes in a high-risk sample: a controlled longitudinal multi-centre study

Abstract: Aim Previous studies have demonstrated a positive effect of school-based life skills programmes on the prevention of substance abuse and other health-risk behaviours in children and adolescents. However, the comparison and interpretation of study results is difficult due to methodological problems. In particular, the effectiveness of such programmes within high-risk groups remains uncertain. In this study, we investigated the effects of two school-based life skills programmes on substance abuse and subjective … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
33
0
3

Year Published

2013
2013
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(36 citation statements)
references
References 18 publications
(20 reference statements)
0
33
0
3
Order By: Relevance
“…As a result of the study, it is observed that the children, who have high point average of social skill, have low pros perception of smoking and have high cons perception of smoking. The researches state that having positive perceptions of their social skills develop children's positive coping and decrease the rate of trying cigarette and smoking by developing negative attitudes towards smoking (Hover and Gafney, 1988;Bandura, 1989;Botvin et al, 1994;Bandura, 1998;Longlios et al, 1999;Schier and ark.1999;Epstein et al, 2000;Griffin et al, 2001;Griffin et al, 2002;De Veries et al, 2003;Epstain et al, 2003;Sarah et al, 2005;Epstein, et al, 2007;Bektas, 2009;Hiemstra et al, 2009;Bektas, et al, 2010a;La Torre et al, 2010;Cremers et al, 2012;Menrath et al, 2012;Spyratos et al, 2012). Bandura (1998) states that when they have positive attitudes about himself/ herself, the children's self-efficacy levels increase, their self-esteem and the level of self-concept advance, and their internal locus of control increases.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…As a result of the study, it is observed that the children, who have high point average of social skill, have low pros perception of smoking and have high cons perception of smoking. The researches state that having positive perceptions of their social skills develop children's positive coping and decrease the rate of trying cigarette and smoking by developing negative attitudes towards smoking (Hover and Gafney, 1988;Bandura, 1989;Botvin et al, 1994;Bandura, 1998;Longlios et al, 1999;Schier and ark.1999;Epstein et al, 2000;Griffin et al, 2001;Griffin et al, 2002;De Veries et al, 2003;Epstain et al, 2003;Sarah et al, 2005;Epstein, et al, 2007;Bektas, 2009;Hiemstra et al, 2009;Bektas, et al, 2010a;La Torre et al, 2010;Cremers et al, 2012;Menrath et al, 2012;Spyratos et al, 2012). Bandura (1998) states that when they have positive attitudes about himself/ herself, the children's self-efficacy levels increase, their self-esteem and the level of self-concept advance, and their internal locus of control increases.…”
Section: Discussionmentioning
confidence: 99%
“…The identification of risk factors associated with smoking initiation and established smoking are crucial in the fight against tobacco products. Studies indicate that there are many determinants which influence the decisions to start or continue smoking, the most prominent being social/ competence skills (Hover and Gafney, 1988;Bandura, 1989;Botvin et al, 1994;Bandura, 1998;Longlios et al, 1999;Schier et al, 1999;Epstein et al, 2000;Griffin et al, 2001;Griffin et al, 2002;De Veries et al, 2003;Epstain et al, 2003;Sarah et al, 2005;Epstein et al, 2007;Bektas, 2009;Hiemstra et al, 2009;Bektas, Ozturk and Armstrong, 2010;La Torre et al, 2010;Cremers, Mercken, Oenema, and de Vries, 2012;Menrath et al, 2012;Spyratos et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Researchers in many jurisdictions have tried to find an effective measure to prevent young people from beginning to smoke and to date, empirical evidence suggest that school-based smoking prevention programs could provide positive effects on adolescents smoking behaviors (Pertusa, 2011;Menrath et al, 2012). It is suggested that school-based smoking prevention programs should be sensitive to participants' cultural, ethnic, and socio-economic background (Shetgiri, 2011;McKennitt and Currie, 2012).…”
Section: Introductionmentioning
confidence: 99%